2017
DOI: 10.1002/lt.24741
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus–infected liver transplant recipients with incidental hepatocellular carcinoma: A prospective multicenter nationwide cohort study

Abstract: There is a lack of data on incidental hepatocellular carcinoma (iHCC) in the setting of liver transplantation (LT) in human immunodeficiency virus (HIV)-infected patients. This study aims to describe the frequency, histopathological characteristics, and outcomes of HIV+ LT recipients with iHCC from a Spanish multicenter cohort in comparison with a matched cohort of LT patients without HIV infection. A total of 15 (6%) out of 271 patients with HIV infection who received LT in Spain from 2002 to 2012 and 38 (5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…HCV recurrence in HIV patients is more aggressive, and liver fibrosis is more rapid due to HAART toxicity [ 25 ]. An increasing body of evidence suggests that treatment for HCV recurrence positively affects graft survival and mortality [ 26 , 27 ]. Unlike HCV coinfection, HIV-infected patients with HBV appear to have better outcomes after OLT when HBV reinfection prophylaxis is properly provided [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCV recurrence in HIV patients is more aggressive, and liver fibrosis is more rapid due to HAART toxicity [ 25 ]. An increasing body of evidence suggests that treatment for HCV recurrence positively affects graft survival and mortality [ 26 , 27 ]. Unlike HCV coinfection, HIV-infected patients with HBV appear to have better outcomes after OLT when HBV reinfection prophylaxis is properly provided [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, survival is not worsened by HIV in liver transplant recipients with hepatocellular carcinoma, being above 65% at five years [ 87 ]. Moreover, incident liver cancer in allografts is not more frequent in the HIV setting [ 88 ]. Outcomes in this population are rapidly improving following the advent of new direct acting antivirals for hepatitis C [ 89 ].…”
Section: Lipodystrophy Metabolic Abnormalities and Cardiovasculamentioning
confidence: 99%
“…As end‐stage liver disease is the main cause of death among patients coinfected with HBV or HCV or with nonviral hepatitis, liver transplantation (LT) became the most feasible way to treat these patients after HAART was implemented in clinical practice [6]. However, cohort studies from the USA [7], Germany [8] and Spain [9,10] showed a post‐LT 5‐year survival rate of only 50–55% in HIV/HCV‐coinfected liver recipients. Post‐LT long‐term survival in HIV/HCV‐coinfected recipients was poorer than in HCV‐monoinfected recipients [11].…”
Section: Introductionmentioning
confidence: 99%